Renewable and Non-Renewable Resources: A Review: Implications of transitioning from non-renewable to renewable energy sources (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper considers the change of an economic system from non renewable to unlimited energy. The Hotelling theorem indicates extracting a non renewable aid in an ideal manner like the source has a tendency to be exhausted when optimally extracted. Nevertheless, it may not be sensible to deplete non-renewable sources of energy that create externalities including Global warming and co2 emissions. The newspaper sets up a canonical development type with damages in the household's welfare performance as well as 2 sources of energy - renewable and non-renewable energy.